Knowledge on HIV/AIDS and attitude of physiotherapists towards patients with HIV/AIDS in the Kingdom of Swaziland - Ndlovu, Siluzile (My University, 2017)
INTRODUCTION: Since the introduction of Anti-retroviral therapy, People Living With HIV/AIDS (PLWHA) now live longer and present with various opportunistic neuro-musculoskeletal and cardio-pulmonary conditions among other complications. This has led to a surge in the number of patients that visit the physiotherapy department presenting with many complications which include mobility problems, neurological deficits, muscle weakness and developmental delay in children among others as experienced by the researcher in the work place. AIM: To determine the knowledge of physiotherapists with regard to HIV/AIDS and their attitude towards HIV/AIDS patients in the Kingdom of Swaziland. METHOD: In this study a quantitative, descriptive cross-sectional survey was used to determine the knowledge and attitudes of Physiotherapists in the management of HIV/AIDS in the Kingdom of Swaziland. RESULTS: The results of the study revealed that physiotherapists in the Kingdom of Swaziland have a good knowledge and a positive attitude towards people living with HIV/AIDS. Amongst other attributes that were looked at in the study it was reported that 100% of the participants were knowledgeable on the complications associated with HIV/AIDS and 94% of the physiotherapists reported that they are familiar with complications that will benefit from physiotherapy. On the attributes related to attitude of physiotherapist towards HIV/AIDS patients the study found that 100% of the physiotherapists reported that they would take precautions and continue seeing the patients. There was no statistical significant relationship between years of experience and attitude (Pearson chi-square =0.25, p-value =0.61), familiarity with commonly used ARVS (Pearson chi square =1.13, p-value =0.76) and familiarity with Universal Precautions (Pearson chi-square =2.55, p-value =0.46).There was no statistically significant relationship between knowledge and attitude (Pearson chi square =1.000, p-value =0.61). CONCLUSION: The study revealed that the physiotherapists have good knowledge on HIV/AIDS and they also have positive attitude towards managing People Living with HIV/AIDS at their respective departments. There is need for the physiotherapy training schools to include HIV/AIDS in their curricula since some of the schools of physiotherapy where the participants trained did not include it during their time of training and the practising physiotherapists need continuing health education on HIV/AIDS. There is a need for the work setting libraries where physiotherapists work to have current books and journals for the physiotherapists to update themselves on issues pertaining to HIV/AIDS and internet access in the departments. The physiotherapists are also encouraged to take the initiative to utilise the libraries in their work settings and get information on HIV/AIDS. Keywords: Knowledge; attitudes; Physiotherapists; HIV/AIDS; Patients
Theses (MPH.) -- University of Limpopo, 2017
Keywords: Physiotherapists; HIV/AIDS; HIV antibodies; AIDS (Disease) - Patients; HIV (Viruses)